Síndrome da pessoa rígida: avaliação de 14 pacientes - Lino, Valeria Cavalcante [UNIFESP] (2016)
Main objective: to describe the characteristics of patients with stiff person syndrome (SPS). Secundary: a) to evaluate clinical and laboratorial findings; b)to identify the best therapeutic responses; c) to identify prognostic factors. Methods: we reviewed medical records and included patients with diagnosis of SPS (January 1989 to May 2015) in Neuromuscular Diseases Section at the Federal University of São Paulo (Unifesp), which had at least: axial stiffness with or without limb involvement; episodic spasms superimposed on the underlying rigidity, precipitated by unexpected external stimuli (tactile stimuli, sudden noises, emotional upset) and absence of any other neurologic disease that could account for rigidity and spasms. This study was approved by the Committee for Ethic in Research of Unifesp and Free and Informed Consent was applied to contactable patients. Compiled data: demographic data; age at symptom onset; time to diagnosis; experts who evaluated the patient and respective diagnosis; examination findings; coexisting diseases, labor capacity.The spasms severity was evaluated based on at Penn scale and a level of disability diagnosis was assigned using the modified Rankin score (RS). Serological (GAD65 antibody), electrophysiological and neuraxial magnetic resonance (nMR) data at the time of initial evaluation were also assessed. Results: Fourteen patients (eight having Classic-SPS; four having Focal-SPS; and two having PLUS-SPS) were GAD65 antibody seropositive; 11 were female(3.6: 1); mean age at symptom onset: 42.57 years; time to diagnosis: on average 43.28 months (Classic-SPS: 46.75 months; Focal-SPS: 15.25 and PLUS-SPS: 85.5). Examination findings: facial hypomimia (28.57%); laryngeal spasms (28.6%); cognitive disorders (50%); increased patellar reflexes (71.43%); muscle stiffness, spasms superimposed on the underlying rigidity, co- contraction of agonist and antagonist muscles (100%); hyperlordosis (50%); impaired gait (100%); pain (78.6%); falls (64.3%); electromyography: involuntary continuous paraspinal motor unity activity (42.85%), co-contraction (28.57%); nMR changes: nodular changes in white matter?s brain (PLUS-SPS with ataxia, one case); accentuation of physiological lumbosacral curvature (two cases). Frequently coexisting diseases: autoimmune diseases: 64.3% (type I diabetes mellitus in 50% and autoimmune thyroid disease in 28.6%) and psychiatric disorders (78.6%). Pharmacologic treatment and the best outcomes: symptomatic benefits: were reported in patients (57,14%) treated with diazepam and baclofen (improvement of RS and subjective symptoms); immunotherapy: nine patients (90%) improved after combination of intravenous immune globulin (IVig) and symptomatic drugs (improvement of RS and subjective symptoms), one patient had improved RS after combination of Ivig and intravenous cyclophosphamide. Conclusion: the study emphasized clinical and laboratory data and has demonstrated the insidious and debilitating clinical evolution ofthis rare syndrome. Patients diagnosed and treated early had better outcomes (reduction of subjective symptoms of muscle stiffness, pain, spasms, andreduction of objective symptoms evaluated by RS). Patients who used diazepam, baclofen and IVig in high doses for longer than six months had betterresponses on motor symptoms.